Research Spotlight: The future of biofuels: is it in the bag?. Issue 5 (September 2012) - Trent, Jonathan; Wiley, Patrick; Tozzi, Sasha; McKuin, Brandi; Reinsch, Sigrid
How and where it will be possible to produce biofuels at a scale that can compete with fossil fuels, without competing with agriculture for water, fertilizer and land, is a fundamental unanswered question. We propose that the answer could be offshore membrane enclosures for growing algae. Microalgae are the fastest growing biomass and best oil producers known; by cultivating microalgae offshore using wastewater as a source of water and nutrients in floating photobioreactors (PBRs), the system would not compete with agriculture. Furthermore, freshwater microalgae clean the wastewater, capture CO2 and, if they accidentally escape, they cannot become invasive species because they cannot thrive in seawater. The seawater supports the PBRs, controls temperature and can be used for forward osmosis to concentrate nutrients and facilitate harvesting. Algae products, wastewater treatment, carbon sequestration and compatible aquaculture support the economics of the system as a whole. The completion of a 2-year feasibility study on prototype PBRs, control systems, biofouling, wastewater treatment, life cycle analysis and energy return on investment sets the stage for future offshore studies.